2011
DOI: 10.1080/02602938.2011.592934
|View full text |Cite
|
Sign up to set email alerts
|

A role for technology in enhancing students’ engagement with feedback

Abstract: (2011). A role for technology in enhancing students' engagement with feedback. Assessment and Evaluation in Higher Education, 37 (8), 963-973. electronic feedback with grades withheld, online grade publication, criteria-based feedback and more traditional feedback methods. Through a series of semi-structured interviews student participants were encouraged to articulate their experiences of feedback. The online publication of grades and feedback and the adaptive release of grades were found to significantly enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 13 publications
(11 reference statements)
3
74
0
Order By: Relevance
“…Assignments can be submitted, human-marked and returned online; Hepplestone et al (2011) review work in this area and describe a system which releases feedback to students but stalls the release of grades to students until they have reflected on the feedback received. This approach significantly enhanced students' engagement with the feedback (Parkin et al 2012). Similarly positive results have been reported for the use of audio feedback (Lunt & Curran 2010) and screencasting , O'Malley 2011.…”
Section: E-assessment Beyond Quizzessupporting
confidence: 50%
“…Assignments can be submitted, human-marked and returned online; Hepplestone et al (2011) review work in this area and describe a system which releases feedback to students but stalls the release of grades to students until they have reflected on the feedback received. This approach significantly enhanced students' engagement with the feedback (Parkin et al 2012). Similarly positive results have been reported for the use of audio feedback (Lunt & Curran 2010) and screencasting , O'Malley 2011.…”
Section: E-assessment Beyond Quizzessupporting
confidence: 50%
“…Researches showed that students most value the feedback which they can use immediately to improve an assessment mark [28]. The online publication of results and feedback and the adaptive release of grades were found to significantly enhance students' engagement [29].…”
Section: A Students' Surveymentioning
confidence: 99%
“…One approach is to withhold the grade from students until they have submitted a reflection on their feedback, including how they will act upon it in future (Parkin et al 2012;Taras 2001). However, this is problematic because, unless changes are made to the formal assessment guidelines to incorporate this approach, it would not be possible to withhold the grade indefinitely from those I. Glover et al…”
Section: Wasted Opportunitiesmentioning
confidence: 99%
“…Tools that allow the easy reuse of standard pieces of feedback, such as the GradeMark tool in Turnitin, make this very straightforward by enabling the criteria to be quickly referenced throughout the feedback. Marking rubric tools can also be used to help link general feedback to the assessment criteria and overall grade (Glover 2012;Parkin et al 2012;McGoldrick and Peterson 2013) and are increasingly becoming an integrated part of the assignment features of VLEs, such as Blackboard and Moodle.…”
Section: Directly Linked To Criteriamentioning
confidence: 99%